Rancang Bangun Prototipe Sistem Jalur Bongkar Muat Cerdas (Smart Loading Zone) - Rizal Aprianto; Dandy Aji Saputra; Yunindra Eka Ariffansyah (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2025)
The rapid growth of cities in Indonesia, especially in market and terminal areas, poses challenges in managing logistics and parking of goods vehicles. The main problem is the limited land that causes vehicles to park haphazardly, resulting in congestion and delays in distribution. This study develops a Smart Loading Zone system based on Arduino Uno, with ultrasonic sensors to detect vehicles, servo motors as automatic portal drivers, and LCD screens to display available parking slot information. After the system was assembled and tested, the results showed that the ultrasonic sensor was able to detect vehicles accurately, while the servo motor and LCD worked according to the specified system logic. The portal opens automatically when a vehicle is detected and slot information is immediately updated on the LCD. This system helps regulate vehicle flow to be more orderly, avoids haphazard parking, and speeds up the loading and unloading process. This system is effective and economical to be applied in dense areas, and supports the smart city concept in micro logistics management. This technology can also be further developed as an IoT-based solution for more efficient distribution management.